Applying enzyme treatments in Bacillus cereus biofilm removal. (15th April 2023) - Yang, Shuo; Wang, Yating; Ren, Fanchong; Li, Zhuosi; Dong, Qingli
Abstract: Bacillus cereus, one of the most frequent causative agents of food poisoning outbreaks, has the ability to produce biofilms and causes serious problems in the food industry. In the food industry, chemical cleaning agents together with clean-in-place techniques are usually used to eliminate biofilms; however, these approaches are not always effective. The use of enzymes is an alternative approach for destroying extracellular polymeric substances, resulting in the destruction of biofilms and causing cell lysis, and has been used in the removal of B. cereus biofilms. To date, a wide range of research has been conducted regarding enzyme treatments on bacterial biofilm removal in different strains of bacteria. However, an overview of enzymatic biofilm removal in B. cereus is still unclear. The extracellular polymeric substance components of B. cereus biofilms, current state of the art for enzyme applications for B. cereus biofilm removal, and factors influencing the enzymatic removal of B. cereus biofilms need to be clarified. To this end, we summarized and discussed the information related to the enzymatic approach for biofilm removal specifically applied in B. cereus strains. Our review illustrated that the compositions of biofilms are heterogeneous due to various B. cereus strains, resulting in different susceptibilities of B. cereus biofilms to EPS-targeting enzymes. In general, enzyme mixtures or chemical-enzyme combinations improved the efficiency of biofilm or cell removal by more than 50%–100%. These findings suggested that enzyme-involved biofilm removal of B. cereus is a feasible approach applied in the food industry. In addition, the diversities of enzyme efficiency are multitudinous factors depended. In turn, this provides an opportunity for the food industry to improve enzymatic efficiency by leveraging these factors. Highlights: Enzymatic approach for biofilm removal in B. cereus strains was reviewed. Enzyme-involved approach can be feasibly applied in the food industry. A mixture of enzymes or a chemical-enzyme combination improved removal efficiency.